The Effect of Using Flashcard Media on the Reading Ability of Class 1 Students at SDN Semolowaru Surabaya - Asrori, Rijal Mu'izzul (BASICA, 2025)
This research aims to determine the effect of flash card media in improving the reading ability of class I students at SDN Semolowaru 1 Surabaya. This research uses a quantitative approach with an experimental design method, namely Pre Experimental Design in the form of One Group Pre-test Post-test Design. The research subjects were class I students at SDN Semolowaru 1 Surabaya. Class 1 students totaling 23 students with 10 male students and 13 female students. The data collection technique uses tests in the form of a pre-test before giving treatment and a post-test after the treatment is given, to compare the results before and after using flash card media. The validity of the instrument used is construct validity using SPSS version 25 tools. Data analysis was carried out using descriptive quantitative analysis techniques and paired t-test. The research results showed three main findings: first, students' reading ability before using flash card media was classified as poor with an average score of 55; second, students' reading ability after using flash card media increased with an average score of 83.5; third, there is a significant influence on students' reading ability after using flash card media, with a significance value of 0.000 < 0.05. Thus, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. This research concludes that the use of flash card media is effective in improving the reading ability of class I students at SDN Semolowaru 1 Surabaya.